Implementation of Project Based Learning with Scratch to Enhance Students’ Computational Thinking on Linear Function - Mas Asfila Aldiyah Sabila; Mariyam Mariyam; Rika Wahyuni (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2025)
This study aims to: (1) determine students’ learning mastery in terms of computational thinking skills, based on a minimum completeness criterion (KKTP) of 70, both individually and classically after the implementation of the Project-Based Learning (PjBL) model assisted by Scratch media; (2) identify whether there is a significant difference in the improvement of computational thinking skills between students taught using the PjBL model with Scratch and those taught through direct instruction on the topic of linear functions at SMP Negeri 19 Singkawang; and (3) observe student learning activities after the application of the PjBL model assisted by Scratch. This quantitative research employed an experimental method using a quasi-experimental design with a nonequivalent control group design. The sample was selected using probability sampling, specifically simple random sampling, resulting in class VIII E as the experimental group and class VIII A as the control group. The findings indicate that: (1) students' computational thinking skills achieved the KKTP threshold both individually and classically after the intervention; (2) a significant difference in skill improvement was found between the experimental and control groups; and (3) students demonstrated active engagement in learning activities following the implementation of the PjBL model assisted by Scratch.